Predictors of student veterans progression and graduation in Veteran to Bachelor of Science in Nursing (VBSN) Programs: A multisite study. - Sikes, Deborah L.; Patterson, Barbara J.; Chargualaf, Katie A.; Elliott, Brenda; Song, Huaxin; Boyd, Jeanean; Armstrong, Myrna L. (Journal of Professional Nursing, 2021)
Capitalizing on the veteran's extensive service experience, values, and norms, Health Resources Services Administration (HRSA) proposed Nurse Education, Practice, Quality and Retention – Veterans' Bachelor of Science (VBSN) Program grants (2016–2019). The purpose was to identify predictors of student veterans' (SV) progression and graduation rates in VBSN programs. A descriptive correlational retrospective design was used. Two hundred and eighty-two (282) SV records were examined. One hundred and forty (140) SVs graduated (49.6%) and 107 (37.9%) were still enrolled. Only program delivery mode (hybrid) was significantly associated with completion and confirmed by logistic regression modeling. An increased representation of SVs' gender, race/ethnicity was present; however, gender, age, race, ethnicity, and veteran status did not significantly predict progression nor graduation. Hybrid program delivery became the single predictor influencing VBSN progression and graduation. As non-traditional students in higher education with a history of social isolation and help-seeking stigma, this delivery mode may have assisted SV retention and persistence. With a registered nurse shortage and workforce calls for increased gender, race, and ethnic diversity, the findings suggest nursing education programs designed for veterans are a viable solution. • Veteran to BSN programs are producing successful nursing education pathways. • Program delivery mode (hybrid) predicted student veterans (SV) program completion. • Faculty can promote SV success through veteran-inclusive teaching/learning strategies. • Military veterans increase gender, race, and ethnic diversity in nursing workforce.